Síntese e caracterização a nível nanométrico da fase Li2(M) Ti308, M=Zn, Co e Ni pelo método Pechini. - Câmara, Maria Suely Costa da (Universidade Federal de São Carlos, 2004)
The present work describes the preparation and characterization of the spinel phases Li2ZnTi3O8, Li2CoTi3O8 and Li2NiTi3O8 synthesized by the polymeric precursor method. Polycrystalline ceramic powders of high quality were synthesized for the Li2ZnTi3O8 and Li2CoTi3O8 phases. The desired spinel phase of the Li2NiTi3O8 compound was not obtained, however the synthesis product consisted of other crystalline phases. The chromatic and luminescent properties of the powders were investigated. The powers were calcined in temperatures between 400oC-1000oC/4h, after the obtention of the puff , in a heat treatment at 400oC/1h. The evolution of the crystalline phases with calcination temperature was investigated by means of X-ray Diffraction and Raman Spectroscopy, where it was verified that the Li2ZnTi3O8 and Li2CoTi3O8 crystalline phases could be obtained at low temperature (500oC). The Rietveld refinement method was used to observe in greater detail the crystalline structures of the spinels, and to study the occupations of the octahedric and tetrahedric lattice sites. The particle characteristics were studied by crystallite size and specific superficial area measurements, scanning electron microscopy and transmission electron microscopy. The results show that the synthesized powders present dimensions in the nanometer scale. The pigment of the Li2CoTi3O8 phase presented a green color for calcination temperatures of 400oC (amorphous) and 500oC (phase with structural defects). In temperatures above 600oC, the pigment presented a green-blue color with stability up to 1250oC. The observed pigment color transition from green to blue is due to the cobalt occupation in tetrahedric and octahedric sites. The Li2NiTi3O8 phase resulted in yellow pigments of excellent stability. The non-crystalline Li2ZnTi3O8 phase presented photoluminescent properties. The crystallization of this material provoked the quenching of the photoluminescent emission. A quantummechanical computer simulation confirms that the non-crystallinity of this material induces the formation of electronic levels, reducing the effective band gap energy when compared to the crystalline phase. This might explain the behavior of the photoluminescence in this spinel phase.
Synthesis and nanometer-scale characterization of the Li2(M)Ti3O8, (M= Zn, Co and Ni) phase obtained by the Pechini method.
Keywords: Físico-química; Espinélio; Método de Pechini; Propriedade fotoluminescente; Propriedades cromáticas; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA